Computed Tomographic Angiography Used for Localization of the Cutaneous Perforators and Selection of Anterolateral Thigh Flap "Bail-Out" Branches. Issue 1 (July 2018) - Steve, Anna K.; White, Colin P.; Alkhawaji, Ali; Hayakawa, Thomas E.J.; Buchel, Edward W.; Morris, Steven F.
Abstract : Background: The purpose of this study was to evaluate the territory supplied by the lateral circumflex femoral artery for the consistency of a proximal perforator that could be used as an alternative pedicle for the anterolateral thigh flap if a tedious intramuscular course is encountered during elevation of the perforator used to develop the initial surgical plan. It is hypothesized that a consistent "bail-out" perforator supplying the proximal thigh would facilitate a simpler anterolateral thigh flap harvest, with minimal modification to flap design. Methods: Computed tomographic images of 9 fresh cadavers were imported using Materialize's Interactive Medical Imaging Control System software to create surface-rendered 3-dimensional reconstructions of 15 lower limbs. Perforators emerging proximally and laterally to a 3-cm radius circle drawn at the midpoint of the anterior superior iliac spine and superolateral patella were considered potential bail-out perforators and evaluated for their number emerging diameter, length, course, and location relative to the anterior superior iliac spine. Results: An average of 2.9 ± 1.8 perforators per limb were identified. Mean pedicle length was 111 ± 20 mm, measured from the origin in the lateral circumflex femoral artery to where the perforators emerged through the deep fascia directly overlying the thigh muscles. Average diameter at origin in the lateral circumflex femoral artery was 2.8 ± 0.8 mm, and that at emergence through the deep fascia was 1.1 ± 0.3 mm. Vessel course was predominantly musculocutaneous (90%). Conclusions: A significant bail-out perforator routinely supplies the proximal anterolateral thigh and may be used as an alternative vascular pedicle for an anterolateral thigh flap if a tedious intramuscular course is encountered during elevation of a perforator identified within the conventional landmarks (3-cm radius circle at the midpoint of the anterior superior iliac spine and superolateral patella).